ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL PERSAMAAN LOGARITMA SISWA KELAS X MIA 1 SMAN 1 SINDUE TOBATA : Analysis of Errors in Solving Logarithm Equation Problems of Class X MIA 1 Students SMAN 1 Sindue Tobata - Alam, Hitman; Paloloang, Baharuddin; Hasbi, Muh.; Rochaminah, Sutji (Aksioma, 2025)
The aim of this research is to obtain a description of the error analysis in solving logarithmic equation questions for Class X MIA 1 SMAN 1 Sindue Tobata students according to the Kastolan indicator. Kastolan indicators include, Conceptual Errors, Procedural Errors, and Technical Errors. This type of research is qualitative research. The subjects in this research were 2 students taken from 24 students of class X MIA 1 SMAN 1 Sindue Tobata in the even semester 2023/2024. Subjects were chosen by considering 1) the student made more mistakes than other students, 2) the errors varied. Data was obtained from the results of written tests and interviews with research subjects. The results of this research show that mistakes made by students in the Kastolan indicators that have been determined are conceptual errors by not being able to choose the formula/property of logarithms correctly. The causal factor is that students do not understand the concept of logarithms presented by the teacher. Procedural errors are indicated by errors in answering questions which result in the steps written by students being wrong and also not being completed until the final answer. The causal factor is that students do not understand how to determine the steps to solve logarithmic equations in their simplest form. Technical errors where students make mistakes in calculating operations or make mistakes in moving numbers or calculation operations from one step to the next, the factor causing this error is that students make mistakes in operating the numbers.